Desain Kurikulum dan Pengembangan PAK dalam Penguatan Iman Katekisasi Berbasis Kearifan Lokal di HKBP Palmarum Tarutung Tahun 2024 - Fransisca Hasugian; Andar Gunawan Pasaribu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to design an innovative and relevant Christian Religious Education (PAK) curriculum for catechism at HKBP Palmarum. This curriculum is designed by integrating local wisdom values ​​to strengthen students' faith. The research method used is a quantitative method. The results of the study indicate that local wisdom is relevant to Christian teachings, PAK material is adjusted to effective learning methods. The curriculum developed is expected to improve students' understanding of Christian teachings, strengthen their relationship with God, and encourage them to apply Christian values ​​in everyday life, while preserving local wisdom values.